Influence of boundary conditions on quantum escape - Georgiou O; Gligorić G; Lazarides A; Oliveira DFM; Bodyfelt JD; Goussev A (My University)
It has recently been established that quantum statistics can play a crucial role in quantum escape. Here we demonstrate that boundary conditions can be equally important - moreover, in certain cases, may lead to a complete suppression of the escape. Our results are exact and hold for arbitrarily many particles. © Copyright EPLA, 2012.
Keywords: 01 Mathematical Sciences; 02 Physical Sciences